Suppressing alignment: Joint PAPR and out-of-band power leakage reduction for OFDM-based systems - Tom, Anas; Şahin, Alphan; Arslan, Hüseyin (Ieee-Inst Electrical Electronics Engineers Inc, 2016)
Orthogonal frequency division multiplexing (OFDM) inherently suffers from two major drawbacks: high out-of-band (OOB) power leakage and high peak-to-average power ratio (PAPR). This paper proposes a novel approach called suppressing alignment for the joint reduction of the OOB power leakage and PAPR. The proposed approach exploits the temporal degrees of freedom provided by the cyclic prefix (CP), a necessary redundancy in OFDM systems, to generate a suppressing signal, that when added to the OFDM symbol, results in marked reduction in both the OOB power leakage and PAPR. Additionally, and in order to not cause any interference to the information data carried by the OFDM symbol, the proposed approach utilizes the wireless channel to perfectly align the suppressing signal with the CP duration at the OFDM receiver. Essentially, maintaining a bit error rate (BER) performance similar to legacy OFDM without requiring any change in the receiver structure.
WOS: 000372844900016
Keywords: Interference Alignment; Out-Of-Band Power Leakage; Peak-To-Average Power Ratio; Sidelobe Suppression; Spectrum Shaping